Policy cycle analysis: a tool for Social Workers : https://doi.org/10.53809/TS_ISS_2022_n.2_31-53 ("Temas Sociais" Journal, 2022)
This article aims to present some theoretical concepts and models of public policy analysis. The aim is to provide social workers with a theoretical analysis of the social policy process with special relevance to the model of analysis of the policy cycle in phases or moments. This option is related to the perspective of the social worker as an implementing agent of public policy, following the perspective of Michael Lipsky (1976, 2010), who considers implementers as active agents with influence on policy, as real "policy makers". Thus, the article presents the three phases of the cycle - formulation, implementation and evaluation - in order to present a general framework that can be operationalised and used as a tool to analyse the policies that these professionals implement. Facing the need to analyse the policy one implements contributes to the politicisation of intervention, through the mobilisation of power in the struggle of forces that characterise the social field, to combat inequality and defend rights and social justice. If this challenge is not taken up, the social services profession may be assumed to be merely executive, abdicating its propositional function and its active role in the formulation, implementation and evaluation of social policies.
Keywords: Public policy analysis; policy process cycle; social work